2015
DOI: 10.1159/000438527
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of Suicidal Erythrocyte Death by Topotecan

Abstract: Background/Aims: The topoisomerase I inhibitor topotecan is used as treatment of various malignancies. The substance is effective by triggering tumor cell apoptosis. In analogy to apoptosis of nucleated cells, erythrocytes may enter eryptosis, a suicidal death characterized by cell shrinkage and cell membrane scrambling with phosphatidylserine translocation to the outer face of the erythrocyte membrane. Signaling leading to eryptosis include Ca2+-entry and ceramide formation. The present study explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(4 citation statements)
references
References 108 publications
0
3
0
1
Order By: Relevance
“…Signaling contributing to stimulation of eryptosis includes activated caspases, stimulated activity of casein kinase 1 α , Janus‐activated kinase JAK3, protein kinase C, and p38 kinase, as well as impaired activity of AMP activated kinase AMPK, cGMP‐dependent protein kinase, mitogen‐activated kinase and stress‐activated kinase MSK, PAK2 kinase, and sorafenib/sunitinib sensitive kinases . Eryptosis is triggered by a wide variety of xenobiotics and enhanced eryptosis is observed in several clinical conditions including dehydration, hyperphosphatemia, chronic kidney disease (CKD), hemolytic‐uremic syndrome, diabetes, hepatic failure, malignancy, sepsis, sickle‐cell disease, beta‐thalassemia, Hb‐C and G6PD‐deficiency, as well as Wilsons disease …”
Section: Introductionmentioning
confidence: 99%
“…Signaling contributing to stimulation of eryptosis includes activated caspases, stimulated activity of casein kinase 1 α , Janus‐activated kinase JAK3, protein kinase C, and p38 kinase, as well as impaired activity of AMP activated kinase AMPK, cGMP‐dependent protein kinase, mitogen‐activated kinase and stress‐activated kinase MSK, PAK2 kinase, and sorafenib/sunitinib sensitive kinases . Eryptosis is triggered by a wide variety of xenobiotics and enhanced eryptosis is observed in several clinical conditions including dehydration, hyperphosphatemia, chronic kidney disease (CKD), hemolytic‐uremic syndrome, diabetes, hepatic failure, malignancy, sepsis, sickle‐cell disease, beta‐thalassemia, Hb‐C and G6PD‐deficiency, as well as Wilsons disease …”
Section: Introductionmentioning
confidence: 99%
“…Eryptosis could be triggered by a myriad of xenobiotics including several cytostatic drugs [ 29 43 ]. Interestingly, both topotecan and cisplatin used for cytostatic treatment of some patients included in this study, have been shown to trigger eryptosis in vitro [ 44 , 45 ]. Notably, patients under platinum-based chemotherapy were shown to have higher risk for anemia as compared to patients with non-platinum based chemotherapy [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, в патогенезе злокачественных новообразований анемии могут вызвать неблагоприятные эффекты после применения цитостатиков [180]. Многочисленные исследования in vitro и in vivo показали, что применение многих химиотерапевтических агентов, включая клофазимин, митоксантрон, блебистатин, руксолитиниб, oксалоплатину, топотекан, регорафениб, оридонин, пицетанол и бипазопаниб, вызывают эриптоз и могут, таким образом, усилить анемию у раковых больных [35,57,73,92,147,182,230,268,269,309].…”
Section: эриптоз как элемент патогенеза анемииunclassified